Challenges and Innovations in Minimally Invasive Surgery for Pediatric Patients in Africa: A Comprehensive Review - Mert Uzun; Nancy S. Zrara; Essey K. Wodajo; Najwa M. Zahra; Magda Wojtara; Olivier Uwishema (Health Science Reports)
ABSTRACT Background Minimally invasive surgery (MIS) has proven to be a successful, developing improvement in surgical practice. Allowing surgeons to operate with minimal incisions, ensures the completion of such procedures with minimal damage to the patient and provides recovery in a shorter time. The use of MIS in the pediatric population has also been growing with the increased involvement of surgeons in the evaluation of training and expertise. In Africa, however, the growth of MIS in the pediatric population faces some obstacles which are in research and innovation, cost, and affordability. Additionally, to the scarcity of resources, the limited number of pediatric surgeons available leads to a substantial workload that affects the quality of care. This paper aims to evaluate the challenges facing MIS in Africa and assess its potential in the future. Methods Data were collected through online databases such as PubMed, Google Scholar, Ovid MEDLINE, and Embase. The research team reviewed all relevant articles regarding MIS in Africa and pediatrics. Results The utilization of MIS in the pediatric population in Africa faces some major challenges. In addition to the limited resources, there is a significantly disproportionate number of physicians per population, and the training received by pediatric surgeons rarely incorporates minimally invasive techniques. This leaves a lot of work to be done to allow better access to MIS on the African continent. The recent advances by Africans in minimally invasive and endoscopic surgical training programs, as well as the establishment of minimally invasive centers, show great promise in the attempt to increase the utilization of MIS in Africa. Conclusions The work done to grow the field of MIS application in Africa is commendable, but efforts need to be strengthened and focus needs to be given to ensure the sustainability of these programs. Furthermore, the work accomplished by countries like Egypt, Senegal, and Nigeria will serve as a huge teaching point to increase the technical expertise of surgeons in the region.